A General Equilibrium Model of Regional Public Goods and Optimizing Subsidies - David A. Vardy (Queen's University, Department of Economics, 1971)
The present paper follows the neoclassical tradition of private goods general equilibrium theory and integrates public goods into a simple equilibrium model. In doing so, no attempt is made to construct a behavioural theory of government to explain the articulation of individual demand for public goods. In what follows, it is assumed that private and public goods are provided by a set of governments and private firms whose market behaviour replicates the long-run equilibrium behaviour of perfectly competitive industries. The paper will use a general equilibrium model to examine the effects of a federal subsidy to a provincial government, which produces a single public good for a province whose population is endogenously determined.
Keywords: 330